Photochemistry of (+)-catechin and (-)-epicatechin - Wilhelm, Anke (University of the Free State, 2008)
Despite the well known fact that photolysis of free phenolic catechins give rise to isomerisation at the C-2 position (e.g. (-)-cis epicatechin converts to the sterically less hindered (-)-trans isomer), researchers have failed to isolate any ring opened compounds via trapping of intermediates with nucleophiles such as methanol or ethanol and radical trap solvents such as 2-propanol. Re-closing of the ring was slow enough to allow bond rotation to yield the observed isomerisation at C-2 but too fast to allow trapping of the intermediate by methanol or 2-propanol. This is unexpected given that thermal ring opening under mild conditions with acid, base or BF3 catalysis had resulted in the isolation of many ring opened species. Our aim was to reinvestigate the photochemistry of free phenolic (+)-catechin, (-)- epicatechin and (+)-fisetinidol at 250 nm and to trap the putative ring opened intermediates with a soft carbon centred nucleophile such as phloroglucinol. Photolysis of (+)-catechin in the presence of phloroglucinol with methanol as solvent resulted in the isolation of the optically active product 1,3-di(2,4,6-trihydroxyphenyl)-1- (3,4-dihydroxyphenyl)propan-2-ol with (1S,2S) absolute configuration and unreacted optically active starting material. Photolysis of (-)-epicatechin under the same conditions resulted in the isolation of the optically active product 1,3-di(2,4,6-trihydroxyphenyl)-1-(3,4-dihydroxyphenyl)propan- 2-ol with (1R,2R) absolute configuration, unreacted optically active starting material (-)- epicatechin, as well as (-)-ent-catechin. The two above mentioned products are enantiomers and have identical NMR spectra, but mirror image CD spectra. The two starting materials, (+)-catechin and (-)-epicatechin, are diastereoisomers and do not have identical NMR spectra. Acetylated (-)-ent-catechin from photolysis of (-)-epicatechin has the same NMR spectra as acetylated (+)-catechin but mirror image CD spectra. Identification of the methoxy-trapped products, 2-((2S,3R)-2-acetoxy-3-(3',4'- diacetoxyphenyl)-3-methoxypropyl)benzene-2',4',6'-triyl triacetate and 2-((2S,3S)-2- acetoxy-3-(3',4'-diacetoxyphenyl)-3-methoxypropyl)benzene-2',4',6'-triyl triacetate, indicates an ionic mechanism, as a radical mechanism would result in a —CH2OH substituted product. The absence of any coupling products in photolysis of (+)-3',4',5,7-tetra-Omethylcatechin, indicates that a free phenolic OH on the 1-position of the B-ring is essential to stabilize the carbocation intermediate long enough for condensation to take place via a quinone methide. Remarkable is the complete stereoselectivity. This indicates that the 3-hydroxy group allows the bulky phloroglucinol group to attack the quinone methide from the antiposition only. Photolysis of (+)-fisetinidol under the same conditions as irradiation of (+)-catechin, yielded the expected propan-2-ol, (1S,2S)-3-(2,4-dihydroxyphenyl)-1-(3,4- dihydroxyphenyl)-1-(2,4,6-trihydroxyphenyl)-propan-2-ol. Our photolytic synthesized products, (1S,2S)-1,3-di(2,4,6-trihydroxyphenyl)-1-(3,4- dihydroxyphenyl)propan-2-ol and (1R,2R)-1,3-di(2,4,6-trihydroxyphenyl)-1-(3,4- dihydroxyphenyl)propan-2-ol, also have a diaryl chromophore in the 1-position. We established an aromatic quadrant based rule to correlate the stereochemistry of the biaryl moiety on C-1 with the sign of the Cotton effect of the CD spectra. This rule is in agreement with previous rules established for 4-arylflavan-3-ols. Photolysis of (+)-3',4',5,7-tetra-O-methylcatechin in methanol and in the presence of 5 eq. phloroglucinol gave no coupling. Isolation of 2-(2-hydroxy-2-methylpropyl)-3,5- dimethoxyphenol in the presence of acetone represents trapping of the o-quinone methide. Irradiation of (+)-3-O-tosyl-3',4',5,7-tetra-O-methylcatechin (better leaving group on C-3) at 300 nm gave (+)-3',4',5,7-tetra-O-methylcatechin. Retention of the absolute configuration at C-3 indicates that fission of the O-S bond took place and not the C-O bond. We postulated that the sulfone group acted as chromophore of the photochemically active compound and not the aromatic rings.
Keywords: Dissertation (M.Sc. (Chemistry))--University of the Free State, 2008; Catechin; Flavonoids; Photochemistry; Phenols